2009
DOI: 10.1249/mss.0b013e318193c64e
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Resistance Training Improves Daily Energy Expenditure and Fat Oxidation

Abstract: Long-term resistance training (RT) may result in a chronic increase in 24-hour energy expenditure (EE) and fat oxidation to a level sufficient to assist in maintaining energy balance and prevent weight gain. However, the impact of a minimal RT program on these parameters in an overweight college age population, a group at high risk for developing obesity, is unknown. Purpose We aimed to evaluate the effect of 6-months of supervised minimal RT in previously sedentary, overweight (mean±SEM, BMI=27.7±0.5kg/m2) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 42 publications
1
68
0
8
Order By: Relevance
“…Some studies have shown increased resting energy expenditure (REE) in response to exercise (6)(7)(8)(9), whereas others have not found any effects (10). These differences might be explained by type, duration, and intensity of the exercise and whether lean body mass increased or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown increased resting energy expenditure (REE) in response to exercise (6)(7)(8)(9), whereas others have not found any effects (10). These differences might be explained by type, duration, and intensity of the exercise and whether lean body mass increased or not.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effect of exercise on fat oxidation has been shown to depend on intensity, duration, and age and body composition of the participants. In this regard, it has been reported that low-tomoderate intensity exercise increases fat oxidation more than does high-intensity aerobic training (12,13); the maximal rate of fat oxidation occurs at a lower percentage of peak oxygen volume (VO 2 peak ) in postpubertal than in pubertal and prepubertal children (14,15); training increased resting fat oxidation in lean adults (16)(17)(18), whereas its influence on resting fat oxidation in overweight and obese adults was inconclusive (6,7,(19)(20)(21). In general, the referenced studies indicate the potential of exercise to increase energy expenditure and fat oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study 29 using similar methods to those reported above but enrolling a sample of younger (mean age, 21±0.5 years), sedentary men and women also found a 7% increase in REE after six months of weight training. Lemmer et al 30 also found a 7% increase in REE after 24 weeks of weight training, regardless of gender or age.…”
Section: Discussionmentioning
confidence: 64%
“…Resistance exercise, on the other hand, has been associated with increased functional capacity that allows participants to engage in additional activities outside the exercise intervention [60][61][62]. Resistance exercise has also been associated with an increase in fat oxidation [63], which could have positive effects on body composition. Another approach, particularly in children, could be a focus on motor development as increased motor competence facilitates the engagement in various physical activities [64].…”
Section: Practical Implicationsmentioning
confidence: 99%